2016
DOI: 10.1080/17583004.2016.1254009
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emissions from land cover change in Central Vietnam

Abstract: The carbon emissions and removals due to land cover changes between 2001 and 2010 in the Vu Gia Thu Bon River Basin, Central Vietnam, were estimated using Landsat satellite images and 3083 forest inventory plots. The net emissions from above-and belowground vegetation biomass were equal to 1.76 § 0.12 Tg CO 2 , about 1.1% of the existing stocks. The vast majority of carbon emissions were due to forest loss, with the conversion of forest to cropland accounting for 67% of net emissions. Forest regrowth had a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…From the analysis of the 3 Landsat images, it was observed that the changes that occurred thus far happened in LULC types of the study area that largely changed from natural environment to modified ecosystems, which further paves the way to complete destruction of natural ecosystems. A previous study, for example, disclosed that of the existing stocks, approximately 1.1% of net C emissions have been documented as a result of LULC change from 2001 to 2010 (Avitabile et al ). That study further revealed that the conversion of forest to agricultural land contributes the largest share of emissions.…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis of the 3 Landsat images, it was observed that the changes that occurred thus far happened in LULC types of the study area that largely changed from natural environment to modified ecosystems, which further paves the way to complete destruction of natural ecosystems. A previous study, for example, disclosed that of the existing stocks, approximately 1.1% of net C emissions have been documented as a result of LULC change from 2001 to 2010 (Avitabile et al ). That study further revealed that the conversion of forest to agricultural land contributes the largest share of emissions.…”
Section: Resultsmentioning
confidence: 99%
“…The RMSE was thus used to generate a probability distribution for each layer by assuming that error was normally distributed unless otherwise noted. In addition, uncertainty associated with LUC extent was derived from the user's accuracy and included in this analysis [51]. Emissions from each C pool were calculated by resampling without replacement each of the input distributions.…”
Section: Emissions Uncertaintymentioning
confidence: 99%
“…It is characterized by a steep topography and the altitude ranges from 0 m at the coast to 2598 m in elevation in the South Truong Son Mountains in the west, and by the Kon Tum mountain mass in the south . Almost half of the land area is covered by forest (47 %), followed by cropland (26 %) and grassland (20 %) (Avitabile et al, 2016). Paddy rice cultivation and livestock farming are the two main agricultural activities in the basin.…”
Section: Introductionmentioning
confidence: 99%